2022
DOI: 10.1029/2022gl099827
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Charge Emission Into Fog From a Remotely Piloted Aircraft

Abstract: Water droplets in air occur commonly in clouds and fogs. The droplets act to remove the molecular cluster-ions generated by radioactivity and cosmic rays. Through this attachment process, droplets acquire a net charge (Gunn, 1954). This can influence their behavior, for example, through modifying collisions and evaporation (Harrison & Ambaum, 2008;Khain et al., 2004). Introducing charge artificially may therefore provide a method of influencing natural droplet systems, with potential applications to fog disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Figure 6 summarises the aircraft trajectories used and presents data obtained from a photodiode sensor carried on the aircraft measuring the reflected sunlight from the fog beneath. Full details are given in [6]…”
Section: Aircraft Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 summarises the aircraft trajectories used and presents data obtained from a photodiode sensor carried on the aircraft measuring the reflected sunlight from the fog beneath. Full details are given in [6]…”
Section: Aircraft Experimentsmentioning
confidence: 99%
“…It has been suggested that the droplet charging influences the properties of the clouds, such as the stability of small droplets, the growth times from cloud droplets to raindrops by coalescence [3] and their reflection of sunlight [4], but this has hardly been investigated in natural water drop systems. To investigate the general possibilities around introducing artificially generated charge into natural droplet systems, real world experiments have been undertaken using corona ion emission into fogs, releasing from within [5] and above [6]. In this paper, the theory underlying the charging of the fog droplets is described (section 2), followed by the effect of charge on droplet evaporation (section 3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The UAV is instrumented with one positive and one negative ioniser, mounted beneath the wings, with ionisers switched on and off under manual control from the UAV pilot. UAV flights over an electric field mill have demonstrated a clear change in electric field during ion emission from the aircraft [5]. Subsequent UAV flights in fog demonstrated a change in the radiative properties of the fog during ion emission periods, as measured by downward-looking radiation sensors onboard the aircraft [5].…”
Section: Introductionmentioning
confidence: 99%
“…UAV flights over an electric field mill have demonstrated a clear change in electric field during ion emission from the aircraft [5]. Subsequent UAV flights in fog demonstrated a change in the radiative properties of the fog during ion emission periods, as measured by downward-looking radiation sensors onboard the aircraft [5].…”
Section: Introductionmentioning
confidence: 99%